New Approaches in the Development of a Vaccine for Mucosal Candidiasis: Progress and Challenges - Vecchiarelli, Anna; Pericolini, Eva; Gabrielli, Elena; Pietrella, Donatella (Frontiers in Microbiology, 2012)
The commensal fungus Candida albicans causes mucosal candidiasis in the rapidly expanding number of immunocompromised patients. Mucosal candidiasis includes orapharyngeal, esophageal, gastrointestinal, and vaginal infections. Vulvovaginal candidiasis (VVC) and antimycotic-refractory recurrent VVC is a frequent problem in healthy child-bearing women. Both these mucosal infections can affect the quality of life and finding new therapeutical and preventive approaches is a challenge. A vaccine against candidal infections would be a new important tool to prevent and/or cure mucosal candidiasis and would be of benefit to many patients. Several Candida antigens have been proposed as vaccine candidates including cell wall components and virulence factors. Here we discuss the recent progress and problems associated with vaccination against mucosal candidiasis.